MP41: Feeling the flow: an evaluation of the GridlockED workshop experience. (May 2019) - Hale, S.; Chan, T.
Abstract : Introduction : GridlockED is an educational (or "serious") game recently developed by a team at McMaster to teach medical learners about patient flow in the emergency department (ED). Beyond patient flow, we were cognizant that the game could provide additional learning opportunities for learners. The goal of this program evaluation project was to investigate workshop attendees' experiences and identify what areas they found most educational.Methods : A GridlockED board game workshop was developed and delivered in several locations over the fall of 2018. Workshops targeted medical learners and were organized by local emergency medicine interest groups. After a standardized video-based introduction to the game concept and rules, the learners played GridlockED for approximately 90 minutes. After the play session, learners completed an anonymous survey consisting of 7-point Likert scale questions about their experience. They were also asked to identify the learning domains for which GridlockED was developed (Patient Flow, Communication and Teamwork, and ED Basics), and were asked via free-text to identify learning objectives from their experience. We received an exemption for this study from our institutional review board.Results : We had 25 respondents (24 medical students and 1 resident). Trainees rated GridlockED as both enjoyable to play and as a meaningful educational experience, with an average rating of 6.56 (SD 0.94) for enjoyability and 6.44 (0.92) for education. When asked what targeted learning domain was most helpful, 45% of students identified patient flow, 37% teamwork and communication, and only 18% ED basics. When asked to identify their top three areas of learning in open-ended responses, students actually identified resource management most frequently (48%), with improved communication skills (40%) as the second most prominent learning objective. Other interesting self-identified learning points were: a greater appreciation of the role of various providers (24%), the unpredictability of ED care (12%), and how things can go wrong (12%).Conclusion : Medical learners find GridlockED to be both enjoyable and educational. In our targeted areas of learning they found patient flow to be the most educational, but self-identified multiple other areas for learning. Students identified resource management and communication as key areas of learning, suggesting that future workshops might be designed specifically to teach these skills.